Planning and Evaluating Educational Work in Slovene Preschools - Marcela Batistič Zorec; Andreja Hočevar (Center for Educational Policy Studies Journal)
The present article examines the changes in Slovene preschools subsequent to Slovenia’s independence in 1991. In the socialist period, the national education programme for preschools was highly structured, goaland content-oriented and subject to schoolization. The Curriculum for Preschools (1999) brought conceptual changes towards education “based on the child” and the process approach, as well as giving more autonomy to preschool teachers and their assistants. In the empirical study, we examine changes in planning and evaluating educational work compared to the past. The results show that the majority of professional workers have reduced the high level of structure and rigidity in planning, and that there is better cooperation between preschool teachers and teachers’ assistants. Unlike in the past, most professional workers regularly evaluate their educational work. As the data was gathered in two phases, before and after the training of professional workers in the Reggio Emilia concept, we also search for the (probably indirect) influences of this training. We conclude that after the training the participation of children in planning and evaluating educational work is higher.